Computer-aided design tool for GT ventilation system ductworks. Issue 2 (4th March 2018) - Furferi, Rocco; Governi, Lapo; Uccheddu, Francesca; Volpe, Yary
ABSTRACT: The design of gas turbine ventilation systems (VSs) is a lengthy and tedious process, often requiring weeks to refine a single design concept and by additional time to manufacture it. This is particularly true when dealing with structural design since the typical approach followed by main worldwide manufacturing companies is to outsource finite elements analysis and, often, the 3d modelling phase itself. Moreover, the structural design process is iterative: the modeling and finite elements analysis steps are repeated several times whenever a new VS has to be produced. Accordingly, speeding-up the structural design phase is today a crucial issue for gas turbine sector. Keeping the above objective in mind, the present paper proposes a CAD-based tool, implemented in a commercial 3D CAD software package (SolidWorks), supporting and partly automating the complex structural VS design process. The solution suggested in this work consists of the design and implementation of a SolidWorks add-in, called DuctWorks, developed by using C# programming language. Differently from commercially available solutions, the proposed tool is specifically thought keeping in mind the necessity of performing a final structural assessment, which is of utmost importance given the considerable dimensions and stresses this kind of VS are subject to in the specific field of GT and energy production industry. Tested against a set of case studies, DuctWorks proved to be effective in allowing designers to accelerate the ventilation systems design process with excellent results when compared with the traditional design process. GRAPHICAL ABSTRACT: